2000
DOI: 10.1109/22.904745
|View full text |Cite
|
Sign up to set email alerts
|

Full-wave analysis of circular microstrip resonators in multilayered media containing uniaxial anisotropic dielectrics, magnetized ferrites, and chiral materials

Abstract: In this paper, Galerkin's method in the Hankel transform domain is applied to the determination of the resonant frequencies, quality factors, and radiation patterns of circular microstrip patch resonators. The metallic patches are assumed to be embedded in a multilayered substrate, which may contain uniaxial anisotropic dielectrics, magnetized ferrites, and/or chiral materials. The numerical results obtained show that important errors can be made in the computation of the resonant frequencies of the resonators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…The experimental results have shown that circular microstrip elements could be easily modified to produce a range of impedances, radiation patterns and frequencies of operation [10]. The studies on circular patch microstrip antennas with anisotropic substrate are in limited number [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results have shown that circular microstrip elements could be easily modified to produce a range of impedances, radiation patterns and frequencies of operation [10]. The studies on circular patch microstrip antennas with anisotropic substrate are in limited number [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Spectral domain analysis has been found to be advantageous in the design of microstrip components such as antennas and resonators providing Green's functions in closed form [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In spectral domain analysis, by imposing the boundary conditions on the transformed field expressions, Green's functions can be determined in rectangular and cylindirical coordinates using Fourier Domain [4-6, 8, 9] or Hankel Trasform Domain formulations [2,3,7,[11][12][13][14][15][16][17][18]. In the case of multilayered substrates and superstrates, such a formulation process requires lengthy field derivations and application of multiple boundary conditions [9,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several composite materials as replacement for metals were studied in many recent studies [6][7][8]. Due to electrical properties and favorable mechanical Carbon Nanotube Composites have been used for electromagnetic applications [9][10][11][12].In this study, using the dyadic Green's function formulation the electric and magnetic fields in the upper half-space due to the current distribution on the Star Patch are obtained [13]. The Sommerfeld-Weyl-type integrals of electric and magnetic fields are calculated in the radiation zone or far-field region [13].…”
Section: Introductionmentioning
confidence: 99%